Erosive osteoarthritis during treatment with bevacizumab and paclitaxel in a patient with recurrent papillary serous carcinoma of the ovary. Issue 2 (1st February 2008) - Jaishuen, A.; Berrios-Rivera, J. P.; Sirisabya, N.; Zheng, H. G.; Li, Y.; Kavanagh, J. J.
Abstract : Bevacizumab (BVC) is currently used in recurrent ovarian cancer and as part of the initial treatment for ovarian cancer. The most serious toxicities associated with BVC include gastrointestinal perforations, delayed wound healing, and hemorrhage. Arthritis had never been addressed in patients who received BVC treatment. This is the first case report of arthritis emergence linked to BVC administration. A 59-year-old female with recurrent ovarian cancer received multiple hormonal and cytotoxic regimens for 5 years and then developed erosive osteoarthritis of the hands secondary to BVC and paclitaxel. This effect was confirmed by a significant improvement in her symptoms and signs, after treatment was discontinued.